A Study of Pregnancies Complicated by Decreased Amniotic Fluid with Maternal and Fetal Outcome in Combined Military Hospital Dhaka - Akter, Mst Ralifa; Haque, Md Anwarul; Nahar, Nargis; Khan, Towhida (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Decreased amniotic fluid volume below the normal range expected for the gestational age is a challenging entity encountered by obstetricians. Normal range of amniotic fluid is Amniotic Fluid Index (AFI) 8-20cm. Amniotic Fluid Index (AFI) is a quantitative estimation of amniotic fluid volume seen and measured by ultrasonography during pregnancy. AFI is the sum of the deepest vertical pocket of fluid, excluding fetal parts and umbilical cord, in four quadrants between the maternal midline vertically and transverse line half way between the pubic symphysis and uterine fundus. Decreased AFI has different etiology, pathophysiology, presentation and effect on fetomaternal outcome. Objectives: To assess the incidence, aetiology, time and mode of delivery as well as to evaluate fetomaternal outcome associated with decreased amniotic fluid. Materials and Methods: Prospective observational study was carried out among 60 cases of pregnancy at 3rd trimester with decreased amniotic fluid index admitted in the Department of Obstetrics and Gynaecology, Combined Military Hospital, Dhaka Bangladesh from October 2012-March 2013. Amniotic fluid index was determined by the four quadrant ultrasonography technique on admission. Variables used are parity, gestational age, AFI, the colour of amniotic fluid, etiology and mode of delivery. Neonatal outcome variables were birth weight, APGAR scores at Iand 5 minutes and admission to the neonatal intensive care unit. Results: This study showed that 6% of the admitted patients were presented with decreased amniotic fluid. Among them 42% were borderline and 58% were severe oligohydramnios. Termination by caesarean section is high especially among the severe oligohydramnios patients 29 of 34. High rate of caesarean section is primarily due to fetal distress 60%. There was no maternal morbidity but there was 32% fetal morbidity. Conclusion: Decreased amniotic fluid volume has no significant effect or maternal morbidity other than increased rate of caesarean section, however there was significant neonatal morbidity mainly due to birth asphyxia, others are neonatal sepsis and meconium aspiration syndrome. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 67-70